Epidermal Growth Factor Network Modulation of Immature Central Nervous System Neuronal Functions and the Inhibitory Effects of Ethanol: Relevance to Fetal Alcohol Spectrum Disorder - Tong, Ming; Monte, Suzanne M. de la (European Journal of Applied Sciences, 2026)
This study characterizes the effects of epidermal growth factor receptor (EGFR) modulation of growth, metabolic activity, and aspartyl-asparaginyl-β-hydroxylase (ASPH) expression in immature central nervous system neuronal cells (PNET2), crosstalk with insulin/insulin-like growth factor (IGF)/insulin receptor substrate (IRS) and Notch networks, and the effects of ethanol exposure on EGFR-regulated responses. Validation studies were conducted with cerebellar tissue and slice cultures from a fetal alcohol spectrum disorder rat model. PNET2 cell growth, viability, metabolic function, and ASPH expression were supported by EGF, TGF-α, and TGF-β. Those effects were associated with increased tyrosine phosphorylation of EGFR. TGF-β exhibited stimulatory crosstalk with the IGF1 pathway and Notch transcription factors, whereas EGF and TGF-α had inhibitory effects on INSULIN and IGF1 receptor and IRS1 mRNA. Ethanol exposure significantly inhibited EGF, TGF-α, and TGF-β-stimulated pY-EGFR, PCNA, and ASPH expression in PNET2 and rat cerebellar slice cultures. The findings herein establish that EGFR pathways regulate critical functions in immature CNS neuronal cells, including ASPH, which mediates cell migration during development. Crosstalk between EGF or TGF-α and insulin/IGF networks was largely inhibitory, whereas between TGF-β and insulin/IGF or Notch networks, the crosstalk was stimulatory. Ethanol’s prominent inhibitory effects on EGFR networks and activation of ASPH likely contribute to the FASD-associated impairments in cerebellar development and function. Therapeutic measures that fortify EGFR signaling through Notch and ASPH may reduce the adverse effects of prenatal alcohol exposure on the brain.